2012
DOI: 10.1089/elj.2012.0152
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Redistricting on Incumbents

Abstract: We analyze the e®ects of redistricting on the electoral fortunes of incumbent legislators, using voting data on U.S. congressional districts, state legislative districts, and statewide races. We¯nd little evidence that redistricting helps incumbents in U.S. legislative elections. If anything, redrawing district lines reduces the average vote margin of those in districted o±ces compared with o±ces that are not districted, reduces electoral security, and increases turnover in the legislature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A visual approach to the first question looks for areas in the literature network where two concepts are discussed separately and where a researcher might posit a connection. For example, recent work (Ansolabehere and Snyder Jr. 2012; Carsey, Winburn, and Berry 2017; Hood and McKee 2013; Limbocker and You 2020) has shown that redrawn lines that change the composition of the electorate exert an exogenous effect on the vote, but less attention has been paid to how such changes affect minority representation; there exists an opportunity for research concerned with political consequences of constituency boundaries to engage more directly with scholarship on minority representation.…”
Section: Application To Redistrictingmentioning
confidence: 99%
“…A visual approach to the first question looks for areas in the literature network where two concepts are discussed separately and where a researcher might posit a connection. For example, recent work (Ansolabehere and Snyder Jr. 2012; Carsey, Winburn, and Berry 2017; Hood and McKee 2013; Limbocker and You 2020) has shown that redrawn lines that change the composition of the electorate exert an exogenous effect on the vote, but less attention has been paid to how such changes affect minority representation; there exists an opportunity for research concerned with political consequences of constituency boundaries to engage more directly with scholarship on minority representation.…”
Section: Application To Redistrictingmentioning
confidence: 99%
“…The first uses simulations to evaluate the fairness of a redistricting plan (Gelman andKing, 1990, 1994a,b;Engstrom, 2006;Glazer et al, 1987;McCarty et al, 2009;Chen and Rodden, 2013;Chen, 2016). The second compares actual election outcomes under different redistricting plans (Brunell and Grofman, 2005;Hetherington et al, 2003;Grainger, 2010;Ansolabehere and Snyder Jr, 2012;Carson et al, 2007;McCarty et al, 2009;Lo, 2013).…”
Section: Related Literaturementioning
confidence: 99%
“…One of the first efforts to elucidate the causes that cause the so-called "marginal seats" in a district is presented in [16]; that is, districts in which the winners win by a small majority, without finding significant links between redistricting and advantages for the incumbents. More recently, [17] analyze the US presidential elections for 1980, 1988 and 2000, both before and after the manipulation of district boundaries; it is empirically demonstrated, from a bipartisan perspective, that, on average, the manipulation of district boundaries had an impact no greater than a 2% advantage for incumbents, and even negatively affecting candidates of a certain party.…”
Section: Introductionmentioning
confidence: 99%